Partnership and Depression in Parkinson’s Disease - S. Seiler; B. Perleth; T. Gasser; G. Ulm; W. H. Oertel; H. Ellgring (Behavioural Neurology)
In this study, the influence of partnership on depression and coping with Parkinson's disease has been investigated. Twenty-three single female patients, 46 married patients (23 female, 23 male) with unimpaired partnership and 42 patients (21 female, 21 male) whose partnership had worsened since the onset of disease, were compared with regard to depression and self reported extent of psychosocial distress. Single female patients tended to have higher depression scores than patients in a stable partnership, especially in items concerning personal worthlessness and senselessness of life. Patients differed in the extent of distress concerning social behavior, psychological problems/anxiety and efficiency. Within the group of single female patients two subgroups emerged: (1) patients with low extent of distress in all aspects; (2) patients who were highly distressed by psychological problems and physical disability but weakly distressed from social interaction. Male and female patients living in a stable partnership reported only a generally low to moderate extent of distress. More than half of the male and female patients who reported an impairment of their relationship also had scores of moderate to severe depression. These patients also had the highest extent of distress in each of the aspects assessed. The results are discussed with regard to possible interactive effects of the disease, quality of the partnership and availability of coping strategies.